2020
DOI: 10.1007/s10067-019-04922-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining genetic risk factors for scleroderma-associated interstitial lung disease

Abstract: Although several genetic associations with scleroderma (SSc) are defined, very little is known on genetic susceptibility to SSc-associated interstitial lung disease (SSc-ILD). A number of common polymorphisms have been associated with SSc-ILD, but most have not been replicated in separate populations. Four SNPs in IRF5, and one in each of STAT4, CD226 and IRAK1, selected as having been previously the most consistently associated with SSc-ILD, were genotyped in 612 SSc patients, of European descent, of whom 394… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In contrast, Sugiura et al (28), in a Japanese population, described that STAT4 rs7574865 was associated with a higher risk of DM/polymyositis (PM) but not with the presence of ILD in this group of patients. This finding is shared with SSc, whereas STAT4 rs7574865 is associated with a higher risk of SSc and is also associated with reduced risk of SSc-related ILD in a Caucasian population (29). Also, in a Chinese Han population, Chen et al (30,31) found two SNPs in ETS1 (rs7117932 and rs6590330) and one SNP in CCL21 (rs951005) associated with a higher risk of DM/PM and with ILD related to IIM.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Sugiura et al (28), in a Japanese population, described that STAT4 rs7574865 was associated with a higher risk of DM/polymyositis (PM) but not with the presence of ILD in this group of patients. This finding is shared with SSc, whereas STAT4 rs7574865 is associated with a higher risk of SSc and is also associated with reduced risk of SSc-related ILD in a Caucasian population (29). Also, in a Chinese Han population, Chen et al (30,31) found two SNPs in ETS1 (rs7117932 and rs6590330) and one SNP in CCL21 (rs951005) associated with a higher risk of DM/PM and with ILD related to IIM.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, the rs2004640T allele and rs10488631 C allele of IRF5 have been identified as risk factors for SSc. Regarding the implications of these findings, associations have been noted between IRF5 rs10488631 and declines in forced vital capacity (FVC) and diffusing capacity of the lungs for carbon monoxide (DLCO) over time, although neither remained significant after Bonferroni correction [61]. The involvement of other IRFs in SSc pathogenesis remains less understood.…”
Section: The Interferon Regulatory Factor Genesmentioning
confidence: 99%
“…Both STAT3 GOF and STAT5B deficiency result in impairment of T reg function, which explains the autoimmune manifestations, but how autoimmunity affects the development of ILD needs further study [79]. Intriguingly, despite all JAK/STAT genetic alterations lead to a bad overcome in ILDs, the STAT4 rs7574865 T allele may be protective against the development of lung fibrosis in SS patients [80].…”
Section: Genetic Alterationsmentioning
confidence: 99%